2017
DOI: 10.1111/1471-0528.14747
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term efficacy of focused ultrasound therapy for non‐neoplastic epithelial disorders of the vulva

Abstract: Objective To investigate the short-and long-term efficacy and influential factors of focused ultrasound for the treatment of nonneoplastic epithelial disorders of the vulva (NNEDV).Design A retrospective observational study.Setting A gynaecologic department in a single centre in China.Population Patients with NNEDV were included in this study: 85 patients were diagnosed with lichen simplex chronicus (LSC), 44 patients with vulva lichen sclerosus (VLS), and seven patients with lichen planus (LP).Methods A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…High‐intensity focused ultrasound involves the delivery of high‐frequency/high‐power ultrasound waves to affected areas while under general anesthesia. One study reported that four of seven patients had complete disease remission as far as 5 years out from treatment, and all seven patients had at least moderate clinical and symptomatic improvement . The specifics of the timeframe were not reported; however, all patients were followed for at least 12 months.…”
Section: Procedural Therapiescontrasting
confidence: 58%
See 1 more Smart Citation
“…High‐intensity focused ultrasound involves the delivery of high‐frequency/high‐power ultrasound waves to affected areas while under general anesthesia. One study reported that four of seven patients had complete disease remission as far as 5 years out from treatment, and all seven patients had at least moderate clinical and symptomatic improvement . The specifics of the timeframe were not reported; however, all patients were followed for at least 12 months.…”
Section: Procedural Therapiescontrasting
confidence: 58%
“…(Step 3) Methotrexate and mycophenolate mofetil have been shown to be effective; however, other options such as hydroxychloroquine, acitretin, and cyclosporine exist. (Step 4) Patients still not responding may benefit from a procedural intervention such as photodynamic therapy or focused ultrasound therapy…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Considering the serious side effects of traditional treatment, high-intensity focused ultrasound (HIFU) treatment, which uses ultrasound as a carrier of energy, has gradually gained popularity as an alternative treatment for VLS [2,4,[12][13][14][15][16]. Propagating harmlessly, HIFU causes a sufficient local rise in temperature for the thermal destruction of target tissues without damaging surrounding or overlying tissues [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HIFU has been used for several other therapeutic applications [13,19]. Recently, several clinical trials have shown that HIFU treatment could relieve itching of the vulva and recover the vulvar skin's elasticity and appearance [12][13][14][15][16]. HIFU appears to be a promising treatment modality for vulvar diseases, including VLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation